The Purpose of Sustainability in Endowment Investment in the Choices of Al-Kamal Ibn Al-Hammam A Comparative Jurisprudential Study (College of Basic Education Research Journal, 2025)
This study addresses topic of " Sustainability in Waqf Investments in  Legal Opinions of Al-Kamal Ibn Al-Humam: A Comparative Jurisprudential Study", exploring  juristic selections of Imam Al-Kamal Ibn Al-Humam in  waqf (endowments) and their role in achieving sustainability to ensure perpetual benefits of waqf in alignment with  objectives of Islamic law.Study begins by clarifying  concept of sustainability in waqf, focusing on Ibn Al-Humam's contributions to establish jurisprudential principles that preserve  continuity of waqf benefits. It examines his stance on investing waqf assets and renewing their resources, highlighting his emphasis on managing waqf to maintain its sustainability and fulfill its intended objectives.Study further explores  impact of Ibn Al-Humam’s views on achieving sustainability, emphasizing his commitment to safeguarding waqf assets and directing their investments towards long-term projects. It also highlights his flexible administrative approach to waqf, ensuring  perpetual realization of societal benefits. Additionally, the study delves into his applications for reviving neglected waqf properties and renewing their functions in line with  objectives of Sharia.A comparison is drawn between Ibn Al-Humam’s opinions and those of other scholars from various Islamic schools of thought, showcasing  distinctiveness of his methodology, which combines flexibility and a profound alignment with Sharia objectives, particularly in ensuring  continuity of waqf returns.Study concludes with recommendations to develop waqf management practices based on Ibn Al-Humam’s methodology, emphasizing  importance of contemporary jurisprudential efforts to enhance  sustainability of waqf as a means of societal development.
Keywords: waqf; sustainability; Al-Kamal Ibn Al-Humam; waqf investment; Sharia objectives; jurisprudential principles; legal opinions; comparative jurisprudence